Application of elicitors (jasmonic acid, salicylic acid and nanosheet) for in vitro growth and biochemical properties of Siam tulip (Curcuma alismatifolia cv. Maejo Impress) - Chumphukam, Orada; Saeyang, Yupha; Baiya, Pimpakay; Duangkon, Nutchanan; Poothong, Sukalya (Agriculture and Natural Resources, 2023)
Importance of the work: The Siam tulip (Curcuma alismatifolia) is an economic crop with the potential for producing bioactive compound through plant tissue culture. Objectives: To investigate the effects of jasmonic acid, salicylic acid and two-dimensional nanomaterials (nanosheets) on the in vitro growth of C. alismatifolia cv. Maejo Impress and its phytochemical properties. Materials & Methods: Two types of elicitors were tested at three concentrations and they were combined with a nanosheet. The control group utilized a basal Murashige and Skoog medium. The experiment units were assigned following a completely randomized design. After 6 wk of culture, growth, total phenolic content and antioxidant activity of the Siam tulip cv. Maejo Impress were studied. Results: The addition of elicitors had no significant effect on the height of explants and new shoots, shoot multiplication and leaf colour. However, the Siam tulip cultured with 4 mg/L and 6 mg/L jasmonic acid (JA) had the highest (p < 0.05) total phenolic content and antioxidant activity compared to those cultured without elicitors. Main finding: The optimal type and concentrations of elicitors were 4–6 mg/L JA for improving the accumulation of bioactive compounds in the micropropagation of C. alismatifolia cv. Maejo Impress without inducing shoot necrosis or death.